The role of higher education towards sustainable consumption behavioural change: topics discussed in sustainable consumption education - João, Isabel (2022)
Many factors have contributed to the urgency of adopting sustainable consumption patterns. The main challenges related to sustainable consumption include respecting our planet in all its complexity and diversity, taking care of communities and life and, to this end, adopting consumption and production patterns that protect human rights and the well-being of communities. The theme of education for sustainable consumption is multidisciplinary with elements from different curriculum topics and addresses all aspects of everyday life. Establishing a common understanding of sustainable consumption education will create a shared understanding of the topic and improve the necessary cooperation between educators and students, making sustainable consumption education an established and more understandable topic. The objective of this study is to identify the main topics within sustainable consumption education teaching and learning, the main barriers and propose some actions that contribute to a sustainable behavioural change in higher education. A literature review was carried out to categorize the main topics related to teaching and learning processes in higher education environments to fill the gap in this underrepresented research topic of education for sustainable consumption. The review allowed the collection of information reported in this new millennium and the identification, selection and critical evaluation of research related to education for sustainable consumption.